THE IMPLEMENTATION OF DUTIES AND FUNCTIONS OF THE VILLAGE COMMUNITY EMPOWERMENT INSTITUTION (LPMK) IN THE IMPLEMENTATION OF DEVELOPMENT IN KIRU-KIRU VILLAGE, SOPPENG RIAJA DISTRICT, BARRU REGENCY - Hj. Aidah; Nur Rahmi A (P3M Stia Al Gazali Barru and Meraja media, 2022)
Copyright (c) 2022 Meraja journal